2023
DOI: 10.3390/jcs7060246
|View full text |Cite
|
Sign up to set email alerts
|

Failure Modes Behavior of Different Strengthening Types of RC Slabs Subjected to Low-Velocity Impact Loading: A Review

Abstract: Concrete is brittle; hence, it is incredibly likely that concrete buildings may fail in both local and global ways under dynamic and impulsive stresses. An extensive review investigation was carried out to examine reinforced concrete (RC) slab behavior under low-velocity impact loading. Significant past research studies that dealt with experimental and numerical simulations and analytical modeling of the RC slabs under impact loading have been presented in this work. As a result, numerous attempts to define fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…For example, Yilmaz et al (Yılmaz et al 2020) found that the impact load decreased as the impactor velocity decreased for RC slabs with different support types. Similarly, Al-Dala'ien et al (Al-Dala'ien et al 2023) reported that the impact load decreased as the impactor velocity decreased for RC slabs with different reinforcement ratios. Moreover, Figure 17 depicts the contour plots of impactor velocity vs. thickness with displacement.…”
Section: Proposed Response Surface Formulationmentioning
confidence: 84%
“…For example, Yilmaz et al (Yılmaz et al 2020) found that the impact load decreased as the impactor velocity decreased for RC slabs with different support types. Similarly, Al-Dala'ien et al (Al-Dala'ien et al 2023) reported that the impact load decreased as the impactor velocity decreased for RC slabs with different reinforcement ratios. Moreover, Figure 17 depicts the contour plots of impactor velocity vs. thickness with displacement.…”
Section: Proposed Response Surface Formulationmentioning
confidence: 84%
“…The relationship between the wall and any given surface is established through contact interaction, utilizing contact models along with the penalty contact approach as a mechanical constraint formulation. It is important to highlight that the cohesive behavior is characterized by the traction-separation relationships that are included as default in Abaqus [57][58]. The friction coefficient assigned to the brick-to-mortar contact is set at 0.75.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…The utilization of non-linear FEA, on the other hand, poses distinct obstacles that must be addressed. These challenges encompass the careful selection of an appropriate mesh specific to the problem at hand, the capability to evaluate the stability of the solution procedure, and the comprehensive assessment of all potential sources of errors attributable to modeling assumptions [10,11,[24][25].…”
Section:  Structural Responsementioning
confidence: 99%